Analisis Desain Visual Branding Kafe “Literacy Coffee” - Fauzie, Muhammad Indra (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
In this era of modernization, many business people have set up business premises such as cafes with designs that uphold high aesthetic values and also have a luxurious impression to attract the interest of consumers who see them. This is different from "literacy coffee", where this cafe is very different from other cafes because it carries the theme of literacy as the main concept in this cafe. Visual communication design is basically a term for describing a media processing process in communicating regarding the expression of ideas or conveying information that can be read or seen. Branding is a variety of activities aimed at building and enlarging the identity of a brand with a very broad scope, including trade names, logos, characters and consumer perceptions of the brand. The research method used in this research is qualitative with a narrative approach. The conclusion of this research is that the visual design contained in this literacy coffee cafe attracts people who see it because in the current era of modernization there is a business place that still carries a classic concept and is a place that is useful for the visiting generation.